Gas adsorption in metal-organic frameworks : fundamentals and applications - Glover, Thomas Grant; Mu, Bin (CRC Press/Taylor & Francis Group, 2018)
The book discusses MOF synthesis and the state of MOF literature and provides guidance on how thermodynamics, mass transfer, packed-bed behavior, and water stability all contribute to gas phase separations and storage in MOFs. Several books on both MOFs and adsorption are available but a text that approaches MOF design, synthesis, and characterization with the intention of performing gas phase separations is absent. This text provides an introduction to MOF synthesis and characterization; adsorption theory including isotherms, mass transfer in porous solids, and fixed-bed wave theory; and discuss applications of MOF materials that illustrate these concepts--